Evaluation of English language improvement program for Information System graduates using a comparative analysis method - Purwasih, Ratih; Rahimullaily, Rahimullaily; Zikri, Zikri (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2023)
STMIK Indonesia Padang seeks to improve the quality of its graduates by providing several academic training in information systems science and soft skills. One of them is training to improve graduates' English skills, including English I and II, English for career, and TOEFL training. The purpose of the study was to evaluate the success of the English language improvement program given to graduates of STMIK Indonesia Padang by comparing the scores for all English programs. This research method is explanatory. Data processing and analysis used descriptive statistics and comparative mean analysis techniques with Friedman test statistics on 4 data groups and Wilcoxon on two data groups. The sample of this study is a saturated sample (170 people) and dependent. The results of the test statistic showed that the value of sig. is less than 0.05. This shows that there is a significant difference between the average scores of English I, English II, English for Career, and TOEFL, either simultaneously or not. Based on descriptive statistics, it was found that the difference did not indicate an increase in the average score on English language skills. Several recommendations can be made in improving English, including (1) the implementation of continuous training, not only at the beginning of the semester and at the end of the semester for students, (2) Increasing the practice of communicating English such as participating in debate competitions, storytelling, and speeches.